Best Practices and Good Governance of Ottoman Empire in Acehnese Manuscript of Hikayat Eseutamu - (Corresponding Author), Fakhriati Fakhriati; Perwira, Reza; Nasri, Daratullaila; Banda, Maria Matildis; Musdikawati, Sri (Journal of Al-Tamaddun, 2025)
Abstract Ancient manuscripts preserve local knowledge and connect the past, present, and future in a global context. Their legacy is considerable because they help in the scientific mapping of what the ancestors left behind. This study aims to analyze the content of an Acehnese manuscript entitled Hikayat Eseutamu, which describes how the Acehnese appreciated the Turkish kingdom in the past. This manuscript exhaustively elaborates on the best practices, good governance, and proper conduct of the Ottoman Empire. Using philological and historical approaches, this study analyzes the content of Hikayat Eseutamu manuscript, which was written in Acehnese, and provides international information about the Acehnese-Turkish relationship. The findings of this study show that the Ottoman Empire was able to convince the Acehnese of the positive connection between diplomacy and social communication at both the governmental and public levels. This study is expected to have a long-term impact on state relations between Turkey and Indonesia.